Penataan dan Pemberdayaan Pedagang Kaki Lima di Kota Medan - Siregar, Deny (Universitas Islam Sumatera Utara, 2024)
In general, the growth of both formal and informal sectors in economic activities is a logical consequence of the development process. The unresolved issues of unemployment, the limited availability of new job opportunities, and the economic pressures to sustain livelihoods have led some individuals to seek alternative employment outside the formal sector. One of the informal sectors widely pursued by the people of Medan City is street vending (PKL). This informal sector generally consists of small-scale businesses with limited capital, scope, and business development. However, the community's demand for street vendors has led to an increasing number of such vendors. Medan City faces challenges similar to those of other major cities in managing, regulating, and supporting street vendors (PKL). Over time, the presence of street vendors in Medan has encroached upon roadways and public facilities, causing disturbances to public order, cleanliness, and traffic flow. This highlights the need for structuring and empowering street vendors to create social order and community harmony. Proper and effective street vendor management can enhance the welfare and competitiveness of the informal sector, transitioning it into the formal sector and improving the overall well-being of the community. Based on these considerations, it is deemed necessary to implement the structuring and empowerment of street vendors.